Analysis of the Implementation of Reproductive Health Prevention in the Islamic Boarding School (Study at Al Ma’ruf Islamic Boarding School – Kediri) - Dessy Lutfiasari; Eko Winarti; Nikmatul Firdaus; Zulfatus Saadah; Pria Sabila Putri (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
There are many special issues about reproductive health. One of the important issues is a special need of reproductive care in woman. This research aims to knowing implementation of preventing health reproductive problem in Islamic Boarding School. The design of this research is the qualitative study on .6 key informant and 2 triangulation informants. Research analysis with content analysis. The result showed that there were three implementations of the prevention of health reproductive problem in adolescent like providing a healthy food, giving health education and providing the environment clean and healthy.